2017
DOI: 10.1007/s11064-017-2274-0
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Contributes to Spinal Long-Term Potentiation and Mechanical Hypersensitivity Via Fyn-Mediated Phosphorylation of NMDA Receptor GluN2B Subunit at Tyrosine 1472 in Rats Following Spinal Nerve Ligation

Abstract: Previously we have demonstrated that brain-derived neurotrophic factor (BDNF) contributes to spinal long-term potentiation (LTP) and pain hypersensitivity through activation of GluN2B-containing N-methyl-D-aspartate (GluN2B-NMDA) receptors in rats following spinal nerve ligation (SNL). However, the molecular mechanisms by which BDNF impacts upon GluN2B-NMDA receptors and spinal LTP still remain unclear. In this study, we first documented that Fyn kinase-mediated phosphorylation of GluN2B subunit at tyrosine 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 73 publications
2
29
0
Order By: Relevance
“…NMDA receptors (Celerier et al, 2000;Corder et al, 2013), adenylyl cyclase (Corder et al, 2013) and protein kinase A are required for latent sensitization, but it is unclear whether they mediate its expression or its maintenance. NMDA receptors in the dorsal horn are potentiated by phosphorylation by the Src family kinase (SFK) Fyn (Guo et al, 2002;Abe et al, 2005;Chen et al, 2010) downstream of the activation of trkB receptors by BDNF (Mizuno et al, 2003;Xu et al, 2006;Geng et al, 2010;Chen et al, 2014;Li et al, 2017). Therefore, we hypothesized that an SFK mediates the maintenance of latent sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…NMDA receptors (Celerier et al, 2000;Corder et al, 2013), adenylyl cyclase (Corder et al, 2013) and protein kinase A are required for latent sensitization, but it is unclear whether they mediate its expression or its maintenance. NMDA receptors in the dorsal horn are potentiated by phosphorylation by the Src family kinase (SFK) Fyn (Guo et al, 2002;Abe et al, 2005;Chen et al, 2010) downstream of the activation of trkB receptors by BDNF (Mizuno et al, 2003;Xu et al, 2006;Geng et al, 2010;Chen et al, 2014;Li et al, 2017). Therefore, we hypothesized that an SFK mediates the maintenance of latent sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…The role of microglial P2X4R in regulating glutamate receptor activation and GABAergic inputs has been thoroughly investigated in neuropathic pain. 4 , 5 , 7 , 8 However, little evidence has been reported for its role in modulating excitatory amino acid transporters (EAATs) in the pathogenesis of neuropathic pain, as well as in migraine chronicity. Sodium-dependent EAATs are divided into five subtypes, namely, EAAT1-5, of which EAAT3 (EAAC1) is expressed in brain stem nuclei and is primarily localized in neurons, with high levels observed at postsynaptic sites.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since the changes induced by SES in paw pressure threshold and C-reflex activity were prevented by administration of CTX-B, a drug that is unable to modify the nociceptive thresholds in normal non-sensitized mice ( Constandil et al, 2012 ), it is likely that the whole process was triggered by the release of BDNF from primary afferents due to SES. This interpretation is supported by the following observations: (i) high-frequency SES, but not low-frequency SES, of afferent sensory nerves at C-fiber intensity causes spinal release of BDNF ( Lever et al, 2001 ); (ii) intrathecal injection of BDNF produces CTX-B-sensitive enduring mechanical hyperalgesia in rats, which imitates that induced by high-frequency SES ( M’Dahoma et al, 2015 ); (iii) full-length TrkB receptors were present at somato-dendritic membranes of lamina II neurons in the rat and mouse dorsal horn ( Salio et al, 2005 ); (iv) binding of BDNF to the TrkB receptor regulates neural response and synaptic function in the dorsal horn output neurons through a variety of neuroplasticity mechanisms, including increased phosphorylation of NMDA receptor subunits NR1 ( Slack et al, 2004 ; Liu et al, 2015 ) and NR2B ( Peng et al, 2012 ; Ding et al, 2015 ; Li et al, 2017 ); (v) activation of NMDA receptors downstream to TrkB signaling is essential for behavioral expression of the mechanical hyperalgesia induced by intrathecal BDNF ( Marcos et al, 2017 ). It is then conceivable that BDNF released by C-fibers during SES application rapidly facilitates the induction of NMDA-dependent early-phase LTP in the spinal cord thereby leading to central sensitization, as reflected by the lower paw pressure threshold and the increased C-reflex activity.…”
Section: Discussionmentioning
confidence: 99%
“…This rather late production of BDNF in spinal cord microglia could result from microglial activators, such as ATP and fractalkine (CX3CL1), which are released from stimulated primary afferent neurons in naïve and hyperalgesic animals (for review see Taves et al, 2013 ) and activate microglia via the corresponding P2X, TrkB, and CX3CR1 receptors and the associated downstream p38 MAPK pathway ( Gong et al, 2009 ; Trang et al, 2009 ; Zhuang et al, 2007 ). It has been shown that microglial derived BDNF contributes to pain hypersensitivity through phosphorylation of the NMDA receptor subunits NR1 via ERK and PKC ( Slack et al, 2004 ) and NR2B via Fyn kinase ( Li et al, 2017 ), and also through the disinhibition of nociceptive processing in the dorsal horn via downregulation of the K + -Cl − cotransporter KCC2 ( Ferrini and De Koninck, 2013 ). Finally, BDNF also triggers long-term neuronal plasticity in the brain, and possibly in the spinal cord, via the activation of TrkB-ERK-CREB cascade, thereby signaling for a multitude of proteins involved in protein synthesis-dependent late-phase LTP ( Minichiello, 2009 ).…”
Section: Discussionmentioning
confidence: 99%